Implementation of Tax Planning to Optimize Income Tax Deductions (PPh Article 21) for Employees of PT Magnum Attack Malang City - Teresiani Jeni Hoang; Hendrik Suhendri; Sri Indah (IRDH International Journal of Social Sciences & Humanities, 2025)
The purpose of this study is to determine the implementation of tax planning to optimize income tax (PPh) Article 21 for employees of PT. Magnum Attack. The research location is where the researcher conducts direct research, observing actual events that occur from the object being studied in order to obtain accurate data. This research was conducted at PT Magnum Attack. The type of research used in this study was a descriptive quantitative approach by describing or depicting the actual state of the research object to identify and analyze the problems faced by the research object and then compare them with existing standards. The data sources used to support this research are primary and secondary data. The data collection methods used by the researcher are observation, interviews, and documentation. The research method used by the researcher in this study is data collected through report studies and literature studies used as guidelines in conducting quantitative analysis. Based on the results of the study, it shows that the alternative to Article 21 income tax deduction that provides the greatest benefit to PT Magnum Attack is the gross-up method. This method excludes employee food and phone allowances from the take-home pay calculation and instead provides catering and vouchers. These costs can be deducted from the company's profit and loss and can be recognized fiscally as a deduction from the income tax payable.